Mental Health Effects of COVID-19 Pandemia: A Review of Clinical and Psychological Traits - Kontoangelos, Konstantinos (Psychiatry Investig, 2020)
OBJECTIVE: As the coronavirus (COVID-19) pandemic sweeps across the world, it is causing widespread concern, fear and stress, all of which are natural and normal reactions to the changing and uncertain situation that everyone finds themselves in. METHODS: In this general review, we examined the literature about the psychological effects of COVID-19 pandemia. In total 65 papers were reviewed using the Medline computer database. Only publications in English were selected. RESULTS: Children are likely to be experiencing worry, anxiety and fear and older people are also those with underlying health conditions, having been identified as more vulnerable to COVID-19, can be extremely frightening and very fear-inducing. China and several other countries took strict isolation measures. Medical staff and affiliated healthcare workers (staff) are under both physical and psychological pressure. CONCLUSION: The COVID-19 pandemic is exceptional. Its effect will likely be imprinted on each individual involved. Extensive stressors will emerge or become worsened. Many medical staff workers will be harmfully psychologically affected.